Hydrogen peroxide maintains the heterogeneous reaction of sulfur dioxide on mineral dust proxy particles - L.B. Huang; Y. Zhao; H. Li; Chen, Z. M. (Atmospheric Environment, 2016)
The heterogeneous oxidation of sulfur dioxide (SO2) on a-Al2O3 particles was investigated using a flow reactor coupled with a transmission-Fourier transform infrared (T-FTIR) spectrometer at different relative humidities (RH) in the absence or presence of hydrogen peroxide (H2O2), with an emphasis on the saturation coverage of SO2 and the timescale on which the reaction reaches saturation. It is found that the saturation coverage of SO2 in the absence of H2O2 increases with rising RH due to the hydrolysis of SO2 by surface adsorbed water. However, the reaction ultimately reaches saturation since the produced sulfite/bisulfite cannot be further converted to sulfate/bisulfate in the absence of oxidants. In addition, the presence of H2O2 can significantly increase the saturation coverage of SO2 by efficiently oxidizing sulfite/bisulfite to sulfate/bisulfate. Under humid conditions, adsorbed water facilitates the hydrolysis of SO2 and mitigates the increase of surface acidity, which can inhibit the hydrolysis of SO2. Hence, in the presence of H2O2, the saturation coverage of SO2 as well as the time of reaction reaching saturation increases with rising RH and the surface is not saturated on the timescale of the experiments (40 h) at 60% RH. Furthermore, the increase of saturation coverage of SO2 in the presence of H2O2 was observed on chemically inactive SiO2 particles, indicating that the hydrolysis of SO2 and subsequent oxidation by H2O2 likely occurs on other types of particles. Our findings are of importance for understanding the role of water vapor and trace gases (e.g., H2O2) in the heterogeneous reaction of SO2 in the atmosphere.